Adolescent coping [ advances in theory, research and practice - Frydenberg, Erica , 1943- (Adolescence and society, 2008)
Highlights the ways in which coping can be measured and details an adolescent coping instrument. This book includes topics such as the different ways in which girls and boys cope, coping in the family, how culture and context determine how young people cope, decisional coping, problem solving and social coping, focusing on practice.